2009
DOI: 10.1007/s11292-009-9071-y
|View full text |Cite
|
Sign up to set email alerts
|

No effects in independent prevention trials: can we reject the cynical view?

Abstract: Recent studies suggest that the reported effect sizes of prevention and intervention trials in criminology are considerably larger when program developers are involved in a study than when trials are conducted by independent researchers. This paper examines the possibility that these differences may be due to systematic bias related to conflict of interest. A review of the evidence shows that the possibility of a substantial problem cannot be currently rejected. Based on a theoretical model about how conflict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 65 publications
1
114
0
5
Order By: Relevance
“…We assessed risk of bias in included studies (as ''high,'' ''low,'' or ''unclear'') using the Cochrane Collaboration tool (Higgins & Green, 2011). We added a category: whether the trial was conducted by researchers independent of the developer (Eisner, 2009).…”
Section: Transporting Parenting Programs Between Countriesmentioning
confidence: 99%
“…We assessed risk of bias in included studies (as ''high,'' ''low,'' or ''unclear'') using the Cochrane Collaboration tool (Higgins & Green, 2011). We added a category: whether the trial was conducted by researchers independent of the developer (Eisner, 2009).…”
Section: Transporting Parenting Programs Between Countriesmentioning
confidence: 99%
“…The Home Office grant required the Jerry Lee team to play a different role in England from the role we had played in Australia. In Canberra, we had served as both "developer" and "evaluator" of the RJC program (Eisner 2009;Sherman and Strang 2009a*). In England, by government policy, the two roles had to be separated.…”
Section: Measuring Treatments and Outcomes: Short And Longmentioning
confidence: 99%
“…The answer in this study is yes, but not in the expected direction. Petrosino and Soydan (2005) and Eisner (2009) have both suggested that there is an effect in which evaluations associated with people who develop programs are likely to show better outcomes than evaluations in which no developer is a collaborator. The definition of a ''developer'' may be somewhat problematic, and the authors do not think of themselves as RJ developers.…”
Section: Authors As Evaluatorsmentioning
confidence: 99%